TIKTOK CONTENT PATTERN: CONTENT SIMILARITY AS A STEP TO INCREASE THE ATTRACTIVENESS VISITS TOURIST DESTINATIONS - Ahmad Kurniawan; Alba Romizal; Muhammad Iqbal Djohan (Politeknik Pariwisata Palembang, 2024)
This research on “TikTok Content Pattern: Content similarity as a step to increase the attractiveness visits tourist destinations” aims to understand and analyze the visual content patterns used by influencers on TikTok in the context of promoting nature tourism destinations. The main focus of the research is on five major themes, namely Visual Aesthetics, Visual Storytelling, Visual of Nature Awesome Beauty, Visual Interaction, and Visual Branding and Identity. Through a thematic analysis approach, this research delves deeper into the key elements contained within each theme, including how visual aesthetics create appeal, how visual storytelling builds a strong narrative, and how visual elements can motivate TikTok users to explore natural tourism destinations. The results of this study provide insight into effective strategies for using visual elements on the TikTok platform to increase user engagement and promote natural tourism destinations. The practical implications of this research can provide valuable guidelines for tourism and marketing practitioners to optimally utilize TikTok's potential to increase the attractiveness of customer visits to natural tourism destinations.